L'analyse morphologique des mots arabes à base des schèmes de surface et de graphes - Said IAZZI (Faculté des Sciences de Rabat, 2021)
Morphological analysis is among the essential in natural language processing tools. In this thesis, we developed two approaches to the morphological analysis of Arabic words.
Morphological analysis of Arabic words based on surface schemes and graphs
Keywords: Sciences de l’ingénieur; Sciences de l’ingénieur